2ln(x)-3=-1

Simple and best practice solution for 2ln(x)-3=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2ln(x)-3=-1 equation:


Simplifying
2ln(x) + -3 = -1

Multiply ln * x
2lnx + -3 = -1

Reorder the terms:
-3 + 2lnx = -1

Solving
-3 + 2lnx = -1

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 2lnx = -1 + 3

Combine like terms: -3 + 3 = 0
0 + 2lnx = -1 + 3
2lnx = -1 + 3

Combine like terms: -1 + 3 = 2
2lnx = 2

Divide each side by '2nx'.
l = n-1x-1

Simplifying
l = n-1x-1

See similar equations:

| 2x-x=x-x+9 | | X=(6/5)x-(8/5) | | 2+10x=32 | | (6/5)x-(8/5) | | X=4(-8-5) | | (6y-14)/2 | | -y/4-12=-28 | | -6x-2=y | | |1/4x-2|=4 | | 16=4z+4 | | v/4-16=-12 | | 6y-14/2 | | 2(x-4)+1=3(2-x) | | (X)(X+8)=240 | | 3+0.1(29-x)=1.6x-(0.4x-3.3) | | 20=12+2q | | 5x-2(3-x)=8 | | 13r=5 | | 2=2f-4 | | 6a^2-11a-10= | | U-2/5=2/3 | | 9=2h+1 | | 7+4x=4x-7 | | y=-x^3+9x^2-24+10 | | X-2/3=4/2/5 | | log[5](-7-4x)=2 | | -7+x+2x=-31 | | 5v^2-11v-1=0 | | X-2/3=4(2/5) | | 6k^2-21k= | | 30e^(t/30)(−ln(2)) | | x-1/3-4=x-9/4 |

Equations solver categories